Economic evaluation of Motor Neuron Diseases: a nationwide cross-sectional analysis in Germany - Heinrich, Felix; Cordts, Isabell; Günther, René; Stolte, Benjamin; Zeller, Daniel; Schröter, Carsten; Weyen, Ute; Regensburger, Martin; Wolf, Joachim; Schneider, Ilka; Hermann, Andreas; Metelmann, Moritz; et al. (Journal of Neurology, 2023)
Background and objectives: Motor Neuron Diseases (MND) are rare diseases but have a high impact on affected individuals and society. This study aims to perform an economic evaluation of MND in Germany. Methods: Primary patient-reported data were collected including individual impairment, the use of medical and non-medical resources, and self-rated Health-Related Quality of Life (HRQoL). Annual socio-economic costs per year as well as Quality-Adjusted Life Years (QALYs) were calculated. Results: 404 patients with a diagnosis of Amyotrophic Lateral Sclerosis (ALS), Spinal Muscular Atrophy (SMA) or Hereditary Spastic Paraplegia (HSP) were enrolled. Total annual costs per patient were estimated at 83,060€ in ALS, 206,856€ in SMA and 27,074€ in HSP. The main cost drivers were informal care (all MND) and disease-modifying treatments (SMA). Self-reported HRQoL was best in patients with HSP (mean EuroQoL Five Dimension Five Level (EQ-5D-5L) index value 0.67) and lowest in SMA patients (mean EQ-5D-5L index value 0.39). QALYs for patients with ALS were estimated to be 1.89 QALYs, 23.08 for patients with HSP and 14.97 for patients with SMA, respectively. Cost-utilities were estimated as follows: 138,960€/QALY for ALS, 525,033€/QALY for SMA, and 49,573€/QALY for HSP. The main predictors of the high cost of illness and low HRQoL were disease progression and loss of individual autonomy. Conclusion: As loss of individual autonomy was the main cost predictor, therapeutic and supportive measures to maintain this autonomy may contribute to reducing high personal burden and also long-term costs, e.g., care dependency and absenteeism from work.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Cost of illness (COI); Cost-utilities; Health-related Quality of Life (HRQoL); Motor Neuron Disease (MND); Quality-adjusted life years (QALYs); Socio-economic burden